2020
DOI: 10.1057/s41267-020-00313-1
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of qualitative comparative analysis (QCA) to international business research

Abstract: International business (IB) researchers have been slow to embrace a configurational approach in hypothesis formulation and empirical analysis. Yet, much of what IB scholars study is inherently configurational: various explanatory factors and their interplay simultaneously determine the outcome(s) studied, such as governance choice or firm-level performance. The mismatch between the nature of the empirical phenomena studied on the one hand, and hypothesis formulation and empirical methods deployed on the other,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
194
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(200 citation statements)
references
References 34 publications
2
194
1
3
Order By: Relevance
“…The intermediate solution presents the major benefit of the QCA; namely, it enables researchers to capture all three aspects of causal complexity: conjunction, equifinality, and causal asymmetry (Misangyi et al, 2017). Equifinality means that different configurations of causal (core and peripheral) conditions (paths) can lead to the same outcome (Fainshmidt, Witt, Aguilera, & Verbeke, 2020). In our study, these configurations form sufficient conditions to achieve high organizational performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate solution presents the major benefit of the QCA; namely, it enables researchers to capture all three aspects of causal complexity: conjunction, equifinality, and causal asymmetry (Misangyi et al, 2017). Equifinality means that different configurations of causal (core and peripheral) conditions (paths) can lead to the same outcome (Fainshmidt, Witt, Aguilera, & Verbeke, 2020). In our study, these configurations form sufficient conditions to achieve high organizational performance.…”
Section: Resultsmentioning
confidence: 99%
“…FsQCA carries on the benefits of both quantitative and qualitative research, as it considers diversity and specificity of each case and reveals patterns common for the whole data array (Woodside, 2013). The fsQCA explicitly allows for equifinality of different combinations of causal conditions (Fainshmidt et al, 2020), which means that more than one combination of causal conditions may be found to be linked to the same outcome (Schneider et al, 2010). We reported several general configurations, which we will use to derive propositions for future research on the link between internationalization and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Fainshmidt et al (2020) strongly encourage international business scholars to adopt the configurational thinking in their studies of complex international business contexts and leverage the beneficial characteristics of fsQCA to overcome the common methodological issues (e.g., small sample size, multi-level variables) which cannot be addressed using traditional analytical techniques. Given the promised benefits, we have recently observed a rapid increase in the number of studies in international business (e.g., Fainshmidt et al 2020;Verbeke et al 2019;Witt and Jackson 2016), strategy (e.g., Fiss 2011; Misangyi and Acharya 2014; Schneider et al 2010) and entrepreneurship (e.g., Stroe et al 2018) utilizing this method to investigate the phenomena with complex causality. For example, Douglas et al (2020) demonstrate how fsQCA complements the correlational methods and reveal complexity and heterogeneity of relationships in entrepreneurial phenomena.…”
Section: Statistical Methods and Analysismentioning
confidence: 99%
“…Recent advances in research on global institutional systems (e.g., Witt, Kabbach de Castro, Amaeshi, Mahroum, Bohle, & Saez, 2018) may be instrumental in decomposing these questions. These effects may then further interact with industry- and organizational-level factors, suggesting that research in this vein may be particularly amenable to configurational research methodologies capable of handling complex patterns of causality, such as fuzzy-set qualitative comparative analysis (Fainshmidt, Witt, Aguilera, & Verbeke, 2020; Greckhamer, Furnari, Fiss, & Aguilera, 2018).…”
mentioning
confidence: 99%